(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Melasma is a great challengefor a dermatologist as its treatment is unsatisfactory and recurrence is high.Treatment of melasma using oral tranexamic acid is a novel concept. Objectives: To compare the efficacy of oral tranexamic acid with routine topical therapies for the treatment of melasma. Materials and Methods: This prospective, interventional, randomized controlled trial was conducted among 130 melasma patients in the Department of Dermatology, Combined Military Hospital, Cumilla from June 2016 to June 2017. The patients were divided into two groups consisting of 65 patients each. The first group (Group A) was given routine treatment measures and oral Tranexamic Acid while the second group (Group B) was treated only with routine topical measures. Capsule Tranexamic Acid was prescribed at a dose of 250 mg twice a day for three months and cases were followed during the course of treatment. The response was evaluated on the basis of Melasma Assessment Severity Index (MASI). Results: Astatistically significant decrease in the mean Melasma Assessment Severity Index from baseline to 8th and 12th weeks was observed among group A patents (11.08±2.91 vs 8.95±2.08 at week 8 and vs. 7.84±2.44 at week 12; (p<0.05 for both). While among group B patients the decrease in mean score was significant at 8 weeks and insignificant at 12 weeks follow up (11.60±3.40 vs 9.9±2.61 at 8 weeks and vs. 9.26±3 at 12 weeks; p<0.05 for former but p>0.05 for later). Conclusion: Oral Tranexamic acid provides rapid and sustained improvement in the treatment of melasma. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 148-151